2017
DOI: 10.1002/14651858.cd007935.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive rehabilitation for adults with traumatic brain injury to improve occupational outcomes

Abstract: Cognitive rehabilitation' is the term used to refer to the training given to people with brain injury to address and improve the specific mental abilities that are impaired. This is usually done to improve return to work, independence in managing daily routines, and quality of life. Review question Does cognitive rehabilitation for people with traumatic brain injury improve their return to work, independence in daily activities, community integration and quality of life? Study characteristics We included nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 71 publications
0
36
0
2
Order By: Relevance
“…The types and content of cognitive rehabilitation offered to TBI patients varied across studies. Cognitive rehabilitation strategies ranged from interventions for self-awareness, interventions for emotional perception, categorization training, specific therapies targeting emotional regulation, problem solving, and attention training or multi-modal compensatory cognitive training to more comprehensive cognitive rehabilitation strategies (Kumar et al, 2017). Therefore, the data generated by this review relate to the effectiveness of aforementioned cognitive rehabilitation interventions on outcomes specified above and not to the efficacy of cognitive rehabilitation in persons with TBI in a broader context.…”
Section: What Was Studied In the Cochrane Review?mentioning
confidence: 99%
See 3 more Smart Citations
“…The types and content of cognitive rehabilitation offered to TBI patients varied across studies. Cognitive rehabilitation strategies ranged from interventions for self-awareness, interventions for emotional perception, categorization training, specific therapies targeting emotional regulation, problem solving, and attention training or multi-modal compensatory cognitive training to more comprehensive cognitive rehabilitation strategies (Kumar et al, 2017). Therefore, the data generated by this review relate to the effectiveness of aforementioned cognitive rehabilitation interventions on outcomes specified above and not to the efficacy of cognitive rehabilitation in persons with TBI in a broader context.…”
Section: What Was Studied In the Cochrane Review?mentioning
confidence: 99%
“…This Cochrane review (Kumar et al, 2017) studied return-to-work as the primary outcome as well as independence in ADL, QoL, and community integration in relation to cognitive rehabilitation in TBI. All of these are very important outcomes relevant to functioning and consequently for TBI neurorecovery rehabilitation.…”
Section: What Are the Implications Of The Cochrane Evidence For Practmentioning
confidence: 99%
See 2 more Smart Citations
“…While this intervention requires further investigation, it encompassed the stroke survivor's ability to observe, assess and change their own behaviour, and to generate strategies to encounter difficulties in real life situations (Skidmore et al, 2015). Looking into the field of traumatic brain injury, a recent systematic review (n=9) investigating cognitive rehabilitation showed insufficient evidence to support cognitive rehabilitation (Kumar et al, 2017).…”
Section: Early Rehabilitation After Strokementioning
confidence: 99%